Experiential Based Counseling Untuk Meningkatan Komitmen Belajar Siswa Sekolah Menengah Atas Di Wilayah Kecamatan Indihiang Kota Tasikmalaya - Agung Nugraha; Aam Imaddudin (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2019)
The long-term goal of this research is the implementation of the development of service guidelines to increase student learning commitment so that they are able to support the optimal development and learning process, and are ready to face various challenges in the life process in the future. The specific objective of this research is to get a real picture of the profile of the development of learning commitment of high school students in the Indihiang District of Tasikmalaya District and the effectiveness of experiential based counseling services to increase student learning commitment. This study uses a quantitative-qualitative approach and uses the quasi-experimental method with pretest-posttest design. Data collection using questionnaires revealed the achievement of student learning commitment which was analyzed by inferential statistical analysis techniques. The results of the study showed an increase of 5.28% commitment to study high school students after participating in the unit of experiential learning activities.